Impact of virtual reality and mirror therapy on balance, muscle strength and quality of life in children with unilateral cerebral palsy: a double blinded randomized comparative study - Samar Salem Korney; Naglaa Ahmed Zaky; Walaa Abd-hakim Abd-El-Nabie (Здоров’я, спорт, реабілітація)
Background and Purpose